Influencia de las restricciones en exportaciones ecuatorianas de derivados de cacao hacia el mercado internacional. - Fierro Orellana, Angel Eduardo (2017)
This research tries to identify the restrictions that have cocoa derivatives in the international markets, so that the main factors that influence the export process were analyzed. It is intended to raise awareness about the restrictions for producers and exporters of cocoa products to start production and manufacture of these products under the regulations demanded by the markets, in addition it is detailed on other aspects related to tariff barriers, non-tariff barriers, Phytosanitary requirements among others. This research begins with the definition and contextualization of the object of study, describing the main cocoa derivatives, about cocoa and its origin, on industrialization in Ecuador, then describes the hypothesis and variables, the facts of interest and Raises the main objective that is focused on determining the restrictions demanded by international markets in the export of Ecuadorian cocoa derivatives and raises the specific objectives, aiming to meet these objectives through the development of this research. In the next chapter called the theoretical-epistemological basis of reference, the description of the research approach is carried out, conducting an analysis of the markets and the forms of commerce that can be carried out with the cocoa derivatives, then the theoretical bases Of the research that relate to the main variables that are the restrictions on exports and cocoa derivatives to the international markets. Regarding the restrictions, it was possible to find out about the tariff barriers that are part of the trade agreements signed in Ecuador, where tariffs are established for products, non-tariff barriers and sanitary and phytosanitary requirements. Regarding cocoa derivatives in international markets, it was possible to know that the main products exported by Ecuador to different countries are chocolate and other food preparations containing cocoa, whole or split cocoa beans, raw or roasted, butter, fat and Cocoa oil, cocoa paste, including defatted cocoa, cocoa powder, not containing added sugar or other sweetening matter, husks, skins and other cocoa waste and main consuming country is Brazil, followed by Argentina, Colombia, United States, Mexico, Countries Basses, among others. In addition, the main companies producing cocoa products in the country such as: Adelcocoa S.A., Agro Manobanda Hermanos S.A., Agroarriba S.A., Aromatic Cocoa Export S.A. Among others, the same ones that are successful in the international market. The methodological process describes the design or tradition of selected research, the process of data collection in research and the categorization system in data analysis. Subsequently we talk about the results of the research where the description and theoretical argumentation of results, the respective conclusions and recommendations are made. Determining that the level of exports of cocoa products maintains commercial flow that has allowed the insertion in new international markets, surpassing the restrictions demanded by the different international markets.